DEVELOPMENT OF EDUCATIONAL MATERIALS WITH THE HELP OF MEDIA TECHNOLOGIES - Sulaymanova Dildora Bakhtiyorovna; Sulaymanova Dildora Bakhtiorovna (Journals Park Publishing, 2024)
The article on the development of educational materials with the help of media technologies shows the impact of the media technologies used in the educational process on the assimilation of students, the assessment of their mastery and the improvement of the results provided in the educational process. the article indicates an important tool that will help media technologies to take their leadership in the educational process in the future, students' mastery and the assessment of their mastery.
Keywords: media technology, educational process, research, interactive, virtual, programming, technology, presentation, platform.